2014
DOI: 10.1016/j.physletb.2014.11.017
|View full text |Cite
|
Sign up to set email alerts
|

The Appell function F1 and Regge string scattering amplitudes

Abstract: We show that each 26D open bosonic Regge string scattering amplitude (RSSA) can be expressed in terms of one single Appell function F 1 in the Regge limit. This result enables us to derive infinite number of recurrence relations among RSSA at arbitrary mass levels, which are conjectured to be related to the known SL(5, C ) dynamical symmetry of F 1 . In addition, we show that these recurrence relations in the Regge limit can be systematically solved so that all RSSA can be expressed in terms of one amplitude. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 37 publications
5
29
0
Order By: Relevance
“…Finally, in constrast to the Regge string spacetime symmetry which was shown to be related to SL(5, C) of the Appell function F 1 [26], here we found that the low energy stringy symmetry is related to SL(4, C) [35] of the Gauss hypergeometry functions 2 F 1 .…”
Section: Jhep05(2016)186supporting
confidence: 57%
See 2 more Smart Citations
“…Finally, in constrast to the Regge string spacetime symmetry which was shown to be related to SL(5, C) of the Appell function F 1 [26], here we found that the low energy stringy symmetry is related to SL(4, C) [35] of the Gauss hypergeometry functions 2 F 1 .…”
Section: Jhep05(2016)186supporting
confidence: 57%
“…For this general case, the s − t channel of the scattering amplitude in the Regge limit was calculated to be [26] R |pn,qm,r l…”
Section: Jhep05(2016)186mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was found that the Regge SSA of three tachyons and one arbitrary string states can be expressed in terms of a sum of Kummer functions U [24][25][26], which soon later were shown to be the first Appell function F 1 [26]. Regge stringy symmetries or recurrence relations [25,26] were then constructed and used to reduce the number of independent Regge SSA from ∞ down to 1.…”
Section: Jhep11(2016)062mentioning
confidence: 99%
“…As a result, SSA and symmetries or relations among SSA of different string states at various limits calculated previously can be rederived. These include the linear relations first conjectured by Gross [1-5] and later corrected and proved in [6][7][8][9][10][11][12] in the hard scattering limit, the recurrence relations in the Regge scattering limit with associated SL(5, C) symmetry [24][25][26] and the extended recurrence relations in the nonrelativistic scattering limit with associated SL(4, C) symmetry [29] discovered recently. Finally, as an application, we calculate a new recurrence relation of SSA which is valid for all energies.…”
mentioning
confidence: 99%